Rapid nucleic acid detection of Escherichia coli O157:H7 based on CRISPR/Cas12a system. (December 2021) - Wang, Shujuan; Fan, Yiling; Feng, Zhen; Song, Minghui; Li, Qiongqiong; Jiang, Bo; Qin, Feng; Liu, Hao; Lan, Lefu; Yang, Meicheng
Abstract: Escherichia coli O157:H7 ( E. coli O157:H7) is one of the most dangerous foodborne pathogens causing severe illnesses in the elderly, children and immunocompromised people. Traditional methods could not meet the detection requirements of high speed, sensitivity, and specificity. The clustered regularly interspaced short palindromic repeats (CRISPR)-based diagnostic is a novel high sensitivity and specificity detection method. In this study, a rapid nucleic acid of Escherichia coli O157:H7 was detected using rfbE gene based on CRISPR/Cas12a system. The limit of detection for DNA and bacterial concentrations was 0.9 pg/μL and 6.5 × 10 4  CFU/mL, respectively. Furthermore, when the initial bacterial inoculum was 14 CFU/mL in the ground beef sample, the target was detected after 4 h of culture through Metal Organic Framework immunomagnetic beads (Fe3 O4 @PDA@UiO-66-NH2 ) enrichment. Highlights: A rapid detection method based on CRISPR/Cas12a system to detect E. coli O157: H7. CRISPR/Cas12a system was more accurate and better than g-MIRA and RT-PCR. CRISPR/Cas12a system demonstrated the limit of 14 CFU⋅mL −1 in beef within 4h. The detection time was 1 h earlier enriched by immunomagnetic beads.